De la question des émotions de l’élève dans la formation enseignante en France - Gaëlle Espinosa (Recherches en Éducation)
This article presents scientific researches on pupil's emotions at school, in relation to school subjects (disciplinary experience) or during disciplinary activities (for example, spelling, grammar and reading comprehension in French, problem solving in mathematics). These researches lead to a better understanding of emotions’ influence in learning. Mainly, they emphasize the disruptive or facilitative nature of emotions in learning and show that emotions play an important role in pupil's knowledge and skills acquisitions and, consequently, both in his experience of success or difficulty and in his well-being or ill-being experience at school. Finally, this article studies the most recent official texts of the French education system (programs and common core of knowledge, skills and culture, 2015) in order to appraise the place given to emotions in these texts, and so, to better think, in the light of these texts and the above-quoted researches, integration’s modalities of the pupil’s emotions question in Vocational Education Training in France.